Corrections to the nomenclature of genus Diatoma (Bacillariophyta: Fragilariaceae) - Blanco Lanza, Saúl; Williams, David M. (Phytotaxa, 2015)
Within plants, algae and fungi, the rules of nomenclature (ICN, McNeill et al. 2012) require that adjectival specific—and infraspecific—epithets agree grammatically (gender concordance) with the generic name. Epithets not conforming to this rule, although validly published, are to be corrected (ICN art. 23.5) without change of the author citation or date. Despite that the original spelling of these epithets is generally to be retained (art. 60.1), improper Latin terminations are always to be changed to accord with, among others, the mentioned art. 23.5 (art. 32.2).